Implementation Challenges Related To Public Management Principles In The South African Public Service (Journal of Namibian Studies : History Politics Culture, 2025)
The objective of the study is to investigate the difficulties that the public service in South Africa faces, with a particular emphasis on the accountability component of good governance. What issues in the public sector prevent the efficient application of accountability principles in the South African context is the question posed. The study uses qualitative desktop analysis of publicly available secondary data to obtain answers. The document analysis was used to analyse the data which was obtained by reviewing official reports. The article's conclusions include the extent of corruption and misconduct that consistently call for the implementation of good governance principles in ministries and departments, as well as the lack of political will to improve openness and accountability in the processes. To name a few, there are also insufficient human resources to ensure responsibility in the hiring and selection of individuals who share normative values. Interventions such as anti-corruption laws and institutional and legislative frameworks are in place to curb wrongdoing and improve accountability. To improve accountability in South African public service ministries and departments, the article suggests an analytical framework known as the Good Governance Framework for Public Service. Its goals are to increase professionalism, public trust, and ethical culture.